PENDEKATAN NONPARAMETRIK UNTUK MENGANALISIS KESEHATAN MENTAL MAHASISWA DALAM KONTEKS PROSES PEMBELAJARAN - Caesar, Muhammad Imamul; Fauzan, Muhammad Al; Faidah, Defi Yusti (LPPM Universitas Bina Bangsa, 2024)
Mental health is a condition where individuals have good emotional, psychological, and social well-being, influencing how they think, feel, and act. This study analyzes the mental health of students aged between 18 and 24 years using a nonparametric statistical approach. Data were collected from a survey of 65 students regarding gender, field of study, and year of study, with a focus on mental disorders such as depression, anxiety, and panic attacks. Descriptive analysis methods and the Chi-Square test with α = 5% showed no significant relationship between gender and mental health disorders. However, a significant relationship was found between field of study and anxiety, while no significant relationship was found between field of study and depression or panic attacks. Additionally, there was no significant relationship between the year of study and any of the mental health disorders examined. These findings provide insights for higher education institutions to design effective policies and interventions to support students' mental health